2018
DOI: 10.1111/liv.13756
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel score for fibrosis staging in patients with chronic hepatitis B

Abstract: FT4 may be an indicator for fibrosis staging in chronic hepatitis B patients. FibroStage is a better model than aspartate transaminase-to-platelet ratio index, fibrosis-4, FibroIndex, Forn, and Lok for the comprehensively diagnosis of significant and advanced fibrosis and cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…GPR is a new noninvasive marker for liver fibrosis in patients with chronic HBV infection despite the diagnostic value of GPR being atypical [10,11,[41][42][43]. Our findings demonstrated the good performance of GPR in predicting significant fibrosis, advanced fibrosis and cirrhosis, with AUROCs of 0.75, 0.74, and 0.80.…”
Section: Discussionmentioning
confidence: 63%
“…GPR is a new noninvasive marker for liver fibrosis in patients with chronic HBV infection despite the diagnostic value of GPR being atypical [10,11,[41][42][43]. Our findings demonstrated the good performance of GPR in predicting significant fibrosis, advanced fibrosis and cirrhosis, with AUROCs of 0.75, 0.74, and 0.80.…”
Section: Discussionmentioning
confidence: 63%
“…A study of 2343 CHB patients revealed that serum ChE was closely correlated with liver fibrosis, and the GCPR model including ChE presented better diagnostic performance than GPR in differentiating significant fibrosis and cirrhosis ( 26 ). Wu et al ( 27 ) also reported that serum ChE was an independent indicator of advanced fibrosis in CHB patients. Of note, serum ChE activity can be affected by several factors, such as obesity, diabetes, uremia, hyperthyroidism, and lipid metabolism disorder ( 24 ).…”
Section: Discussionmentioning
confidence: 93%
“…It was reported that thyroid function was a good index of hepatic function, and that levels of thyroid hormones could be used as indicators to evaluate severity of liver injury in CHB patients. [14][15][16][17][18] Several studies have suggested a potential relationship between thyroid function and inflammatory activity in liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…During liver injury, thyroid dysfunction will occur. [14][15][16][17][18] However, the patterns of thyroid hormone abnormalities vary markedly among patients. Bano et al 13 found that higher TSH levels were a risk factor for fibrosis in patients with nonalcoholic fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation